2019
DOI: 10.1038/s41420-019-0153-y
|View full text |Cite
|
Sign up to set email alerts
|

Long-term impact of maternal high-fat diet on offspring cardiac health: role of micro-RNA biogenesis

Abstract: Heart failure is a worldwide leading cause of death. Diet and obesity are particularly of high concern in heart disease etiology. Gravely, altered nutrition during developmental windows of vulnerability can have long-term impact on heart health; however, the underlying mechanisms are poorly understood. In the understanding of the initiation of chronic diseases related to developmental exposure to environmental challenges, deregulations in epigenetic mechanisms including micro-RNAs have been proposed as key eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 53 publications
4
31
0
Order By: Relevance
“…HFD could also adversely affect the brain by impairing cognitive functions or promoting depression-like symptoms [3][4][5]. Several animal studies have demonstrated that dietary shifts from HFD to a balanced diet could correct adverse effects resulted from HFD with permanent or transgenerational bene ts [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…HFD could also adversely affect the brain by impairing cognitive functions or promoting depression-like symptoms [3][4][5]. Several animal studies have demonstrated that dietary shifts from HFD to a balanced diet could correct adverse effects resulted from HFD with permanent or transgenerational bene ts [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…At PND 77, 18 male rats per group of diet were euthanized with CO 2 . The set of animals used in this study is the same as the one previously described [12].…”
Section: In Vivo Experimental Studiesmentioning
confidence: 99%
“…During the heart development, these epigenetic mechanisms regulate the different steps involving coordinated cellular proliferation, migration, differentiation and programmed cell death, structural remodeling including looping and septation [11]. As a first step in the understanding of epigenetic programming of adult cardiac diseases by early exposure to nutritional excess, we previously highlighted the potential role of microRNAs in cardiac hypertrophy and fibrosis induced by maternal high-fat diet [12]. The decrease in DiGeorge syndrome critical region 8 (Dgcr8) expression, involved in microRNA biogenesis, seemed to be a critical point in the alterations of the microRNA profile and the transforming growth factor beta (TGFβ)-mediated remodeling induced by maternal exposure to high-fat diet [12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations